Exploring the English-Speaking Challenges Faced by an Autistic Student in an Inclusive Classroom Setting - Pratiwi Hawa; Ahmad Amin Dalimunthe (Universitas Islam Negeri Palopo, 2026)
This study explored the English-speaking challenges experienced by an autistic student in an inclusive classroom setting and identified the internal and external factors influencing the student's speaking development. A qualitative case study design was employed to obtain an in-depth understanding of the participant's English-speaking experiences. The study was conducted at an Integrated Islamic Senior High School in North Sumatera and involved three participants: one autistic student, one English teacher, and one shadow teacher. Data were collected through classroom observations, semi-structured interviews, and document analysis and were analyzed using Braun and Clarke's (2006) thematic analysis. The findings revealed that the autistic student experienced several English-speaking challenges, including difficulties in vocabulary retention, sentence construction, speaking fluency, and responding to questions. Although the student demonstrated relatively good pronunciation when using familiar vocabulary and singing English songs, spontaneous communication remained challenging. The study also identified several internal factors affecting speaking development, including attention and concentration difficulties, delayed information processing, and individual learning characteristics. Furthermore, external factors such as teacher support, shadow teacher assistance, family involvement, and a supportive classroom environment played important roles in facilitating the student's speaking development. The study concludes that the English-speaking challenges experienced by the autistic student were influenced by a combination of linguistic, cognitive, and environmental factors. Therefore, individualized support, adaptive teaching strategies, and collaborative educational practices are essential for promoting effective English language learning in inclusive classrooms